New record of jaguar, Panthera onca, in central Colima state, México - Adrián-Gomez, Edgar; Hernández-Jiménez, Carlos Alberto; Zarza, Heliot (Therya Notes, 2025)
The jaguar (Panthera onca) is an endangered species due to habitat loss and illegal hunting throughout its range. In the state of Colima, México, the latest sightings date back to the late 1960s. Here we report a new record for the center of the state. As part of a study to evaluate the diversity of mammals in the buffer area of the Holcim Cement Plant in Tecomán, Colima, 12 camera traps were installed on trees at a height of approximately 50 cm from the ground along trails, separated by 500 m between each other; traps operated 24 hr, 7 days a week between October 2019 and May 2023. After a sampling effort of 16,056 camera-days, 1 adult male jaguar was captured in a low deciduous forest in the town of Caleras on 29 March 2023. The record reported here confirms the presence of jaguars in central Colima. This record is located 50 km south of the previous report of the species for the state in 1969. Sampling in the conserved and buffer areas in the state of Colima is necessary to evaluate the conservation status of the jaguar and identify potential ecological corridors in the state and at the regional level.